The effectiveness of multimedia in teaching planning and colors (Journal of the College of Basic Education, 2022)
The means of cognitive technology and theories of learning and education have evolved with the development of the multimedia approach, and it has become a phenomenon that has its implications, justifications, and effects on the learning and teaching processes, linked with the rapid developments in the past years in the fields of computer technologies, multimedia, and the Internet, and the integration between them, to the emergence of what is called today information and communication technologies (TIC). Its use led to the discovery of new possibilities that were not known before, and its impact appeared clearly in all areas of daily life, including the field of education, because of its many advantages in saving effort, time and money.